Electrochemical characterization of sol-gel hybrid coatings in cobalt-based alloys for orthopaedic implants - Amato, Luis Eduardo Javier (2005)
Cobalt-based alloys are widely used for the fabrication of several devices that are surgically implanted in the body due to their good corrosion and wear resistance as well as their good biocompatibility. However, the carcinogenic potential of metal elements used in total hip arthoplasty components is a concern. This work describes the development of hybrid coatings containing methyltriethoxysilane (MTES) and tetraethylorthosilicate (TEOS) acidic sol, applied by the dip coating method onto ASTM F75 alloys sintered at 450 °C and 550 °C. The performance of the coated metal was evaluated in vitro by classical electrochemical techniques and compared to the uncoated material.